Occupational Contact Dermatitis Risk Factors on Healthcare Workers Isolation Ward During the COVID-19 Pandemic - Yuindartanto, Andre; Sawitri; Astindari; Damayanti; Anggraen, Sylvia; Umborowati, Menul Ayu; Zulkarnain, Iskandar; Listiawan, M. Yulianto; Hidayati, Afif Nurul; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2023)
Background: After a history of exposure to the suspected material and a thorough physical examination, the diagnosis of occupational contact dermatitis (OCD) is commonly suspected. During the initial consultation, essential information involving the above is frequently neglected. Purpose: To evaluate the clinical manifestations of OCD cases in health workers and analyze the factors that influence OCD cases in health workers at the isolation ward of Dr. Soetomo Surabaya Hospital during the COVID-19 pandemic. Methods: The sample selection was done through purposive sampling. Accessible population that met the inclusion criteria and did not have exclusion criteria were included as research samples. The target population was healthcare workers in the Special Isolation Ward of Dr. Soetomo Hospital Surabaya. The accessible population was healthcare workers who performed hand hygiene activities and used Personal Protective Equipment (PPE) in the Special Isolation Ward of Dr. Soetomo Hospital Surabaya. The research subjects were healthcare workers who worked in the Special Isolation Ward. Result: The research results showed a strong and significant correlation between atopic history and the occurrence of contact dermatitis due to poor skin barrier function and decreased tolerance. The study also found that there was no significant correlation between atopic history and the severity level of OCD. There was a significant difference in transepidermal water loss (TEWL) values in the lesion and non-lesion areas, both on the palmar and dorsal aspects of the hand. Moisturizer is an important component in managing hand dermatitis as it can repair and maintain the skin's protective barrier. Conclusion: